A transition metal sulfide and preparation method thereof
By irradiating the multi-layer TMDs, the eccentric chalcogen atoms and P-type doping is solved, and the transformation from indirect bandgap semiconductor to direct bandgap semiconductor is achieved, which significantly improves the optics performance.
Patent Information
- Application Number
- CN202111089122.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-09-16
AI Technical Summary
Multilayer transition metal sulfides (TMDs) have low luminous efficiency, limiting the performance of optoelectronic devices.
By preparing N-layer transition metal sulfides on the substrate and irradiating particles, an eccentric chalcogen atoms are generated to increase the layer spacing, and P-type doping is promoted by adsorbing water molecules or oxygen elements in the air, thereby promoting the exciton state to improve luminous efficiency.
The luminescence efficiency of multi-layer TMDs is improved, prompting them to transform from an indirect bandgap semiconductor to a direct bandgap semiconductor, significantly improving optical performance.
Smart Images

Figure CN115818717B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of semiconductor technology, and in particular to a transition metal sulfide and a preparation method thereof. Background Art
[0002] Transition Metal Dichalcogenides (TMDs) are new two-dimensional materials after graphene, with unique electrical and optical properties. The chemical formula of TMDs can be written as MX2, where M represents a transition metal element and X represents a chalcogen element. TMDs are easy to integrate with Si-based devices and can also be used on flexible substrates. They have broad application prospects in optoelectronic devices such as sensing, communication, and detection, such as photodetectors, gas sensors, piezoelectric devices, and other optoelectronic and nanoelectronic devices. For optoelectronic devices, the luminous efficiency determines the performance of the device, so the luminous efficiency of TMDs is particularly important. Single-layer TMDs are direct bandgap semiconductors with high luminous efficiency, but because single-layer TMDs are too thin, the absorption rate of light is too low; as the number of layers increases, multilayer TMDs transform into indirect bandgap semiconductors with low luminous efficiency, which has a great limitation on the performance of TMDs optoelectronic devices. Summary of the invention
[0003] The present invention provides a transition metal sulfide and a preparation method thereof, so as to solve or partially solve the technical problem that the luminescence efficiency of multilayer TMDs is low.
[0004] In order to solve the above technical problems, the present invention provides a method for preparing transition metal sulfide, comprising:
[0005] Prepare N layers of transition metal sulfide on a substrate to obtain a sample to be processed; N ≥ 2 and is an integer;
[0006] The sample to be processed is subjected to particle irradiation.
[0007] Optionally, the step of irradiating the sample to be processed with particles includes:
[0008] The sample to be processed is subjected to proton irradiation.
[0009] Furthermore, the proton irradiation of the sample to be processed includes:
[0010] The sample to be processed is irradiated with protons, and the proton injection amount is controlled to be 10 12 p / cm 2 Up to 10 15 p / cm 2 .
[0011] Optionally, the step of irradiating the sample to be processed with particles includes:
[0012] The sample to be processed is subjected to neutron irradiation.
[0013] Furthermore, the neutron irradiation of the sample to be processed includes:
[0014] The sample to be processed is irradiated with neutrons, and the neutron injection amount is controlled to be 5×10 8 n / cm 2 Up to 10 10 n / cm 2 .
[0015] Optionally, the transition metal sulfide is one of molybdenum disulfide, tungsten disulfide, molybdenum diselenide and tungsten diselenide.
[0016] Optionally, the substrate is a silicon-oxide substrate, and the oxide is one of silicon dioxide, silicon nitride, hafnium dioxide, and aluminum oxide.
[0017] Optionally, the step of preparing N layers of transition metal sulfide on the substrate to obtain a sample to be processed comprises:
[0018] Adhesive tape and transition metal sulfide bulk material are used to prepare N layers of transition metal sulfide on the substrate through a mechanical stripping method to obtain the sample to be processed.
[0019] Optionally, the step of preparing N layers of transition metal sulfide on the substrate to obtain a sample to be processed comprises:
[0020] N layers of transition metal sulfide are prepared on the substrate by a chemical vapor deposition method to obtain the sample to be processed.
[0021] According to another optional embodiment of the present invention, a transition metal sulfide is provided, wherein the transition metal sulfide is obtained by the preparation method in the aforementioned technical solution.
[0022] Through one or more technical solutions of the present invention, the present invention has the following beneficial effects or advantages:
[0023] The present invention provides a method for preparing transition metal sulfides. By subjecting TMDs to particle irradiation, on the one hand, ex-situ chalcogen atoms can be generated in multilayer TMDs, and these ex-situ chalcogen atoms can enter the interlayer position of MX2, thereby increasing the interlayer distance of XMX, reducing the interlayer force, and promoting the multilayer TMDs to be transformed from an indirect bandgap semiconductor to a direct bandgap semiconductor material, thereby improving the luminescence efficiency; on the other hand, during the particle irradiation process, the multilayer TMDs can adsorb water molecules or oxygen elements in the air, and promote the transformation of negatively charged trion excitons in the multilayer TMDs into neutral excitons by P-type doping, thereby improving the luminescence efficiency.
[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0026] Figure 1 A schematic flow chart of a method for preparing a transition metal sulfide according to the present invention is shown;
[0027] Figure 2 shows a schematic diagram of particle irradiation of TMDs according to the present invention;
[0028] Figure 3 A comparison of PL spectra according to Example 1 of the present invention and Comparative Example 1 is shown;
[0029] Figure 4 A comparison diagram of PL spectra according to Example 2 of the present invention and Comparative Example 2 is shown;
[0030] Figure 5 A comparison of PL spectra according to Example 3 of the present invention and Comparative Example 3 is shown;
[0031] Figure 6 A comparison of PL spectra of Example 4 according to the present invention and Comparative Example 4 is shown. DETAILED DESCRIPTION
[0032] In order to make the technical personnel in the technical field to which the present application belongs more clearly understand the present application, the technical solution of the present application is described in detail by specific embodiments in conjunction with the accompanying drawings. Throughout the specification, unless otherwise specified, the terms used herein should be understood as the meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as the general understanding of the technical personnel in the field to which the present invention belongs. If there is a contradiction, this specification takes precedence. Unless otherwise specified, the various equipment used in the present invention, etc., can be purchased from the market or can be prepared by existing methods.
[0033] In order to solve the problem of low luminescence efficiency of multilayer TMDS, the present invention provides a method for preparing transition metal sulfide, such as Figure 1As shown, the overall idea is as follows:
[0034] S1: preparing N layers of transition metal sulfide on a substrate to obtain a sample to be processed; N ≥ 2 and is an integer;
[0035] S2: performing particle irradiation on the sample to be processed.
[0036] The principle by which the above scheme can improve the luminescence efficiency of multilayer TMDs is as follows: during the particle irradiation process, on the one hand, exosodic chalcogen atoms can be generated in the multilayer TMDs, and these exosodic chalcogen atoms can enter the interlayer position of MX2, thereby increasing the interlayer spacing of XMX, reducing the interlayer force, and promoting the multilayer TMDs to transform from indirect bandgap semiconductors to direct bandgap semiconductor materials, thereby improving the luminescence efficiency; on the other hand, during the particle irradiation process, multilayer TMDs can adsorb water molecules or oxygen elements in the air, and promote the transformation of negatively charged trion excitons in the multilayer TMDs into neutral excitons by P-type doping, thereby improving the luminescence efficiency.
[0037] In some optional embodiments, when the sample to be treated is subjected to particle irradiation, high-energy particle irradiation schemes such as neutron irradiation, proton irradiation or ion irradiation can be selected. Their modification mechanisms for multilayer TMDs are similar, except that the degree of influence on the same TMDs material is different under the same energy and the same particle fluence. Considering the different types of TMDs two-dimensional materials (such as MoS2 or WS2), different numbers of layers, and different irradiation environments, the appropriate particle fluence needs to be determined in combination with different implementation cases.
[0038] Taking MoS2 and neutron irradiation as an example, studies have shown that for neutron irradiation, the defects generated by irradiation at low fluence are mainly sulfur vacancies (Vs). The introduction of Vs will introduce deep defect energy levels in the band gap of MoS2, which will act as non-radiative recombination centers and cause the deterioration of the optical properties of MoS2. However, as the fluence increases, although Vs is generated, since neutron irradiation is carried out in the air, water and oxygen in the air can be adsorbed simultaneously during the irradiation process, thereby repairing Vs and performing P-type doping. P-type doping can promote the transformation of negatively charged trion excitons to neutral excitons, thereby improving the luminescence efficiency, because the luminescence efficiency of neutral excitons is higher than that of trion excitons. However, as the fluence increases further, the displacement damage intensifies, the crystallinity of MoS2 decreases, and its structural integrity is severely damaged, which ultimately leads to a significant deterioration of the optical properties. Therefore, when neutron irradiation is performed, the neutron injection amount can be controlled to 5×10 8 n / cm 2 Up to 10 10 n / cm 2 The preferred injection volume can be 5×10 8 n / cm2 , 3.2×10 9 n / cm 2 , 5×10 9 n / cm 2 wait.
[0039] Taking MoS2 and proton irradiation as an example, studies have shown that the improvement in optical properties is mainly achieved by irradiation-induced transformation of multilayer MoS2 from an indirect band gap semiconductor to a direct band gap semiconductor. Proton irradiation can cause multilayer MoS2 to transform from an indirect band gap semiconductor to a direct band gap semiconductor material. The reason for the transformation is that a certain number of exocytotic sulfur atoms are produced during proton irradiation. These sulfur atoms enter the interlayer positions of multilayer MoS2, increasing the interlayer distance of MoS2 and reducing the interlayer force, thereby forming a "quasi-single-layer" structure, which transforms multilayer MoS2 from an indirect band gap to a direct band gap semiconductor, ultimately improving the optical properties. However, as the proton injection rate increases further, when the degree of degradation of the optical properties caused by displacement damage is greater than the improvement brought about by the transformation of multilayer MoS2 to a direct band gap semiconductor, the optical properties after irradiation will deteriorate. Therefore, when proton irradiation is performed, the proton injection rate can be controlled to 10 12 p / cm 2 Up to 10 15 p / cm 2 The preferred injection volume can be 5×10 12 p / cm 2 , 5×10 13 p / cm 2 , 5×10 14 p / cm 2 wait.
[0040] Since TMDs:MX2 have similar structures and similar properties, the high-energy particle irradiation modification method provided by the present invention can also modify the luminescence properties of TMDs two-dimensional materials such as tungsten disulfide (WS2), molybdenum diselenide (MoSe2), and tungsten diselenide (WSe2).
[0041] In some optional embodiments, the substrate used may be a silicon-oxide substrate, a silicon carbide-oxide substrate or a sapphire-oxide substrate, preferably a silicon-oxide substrate. The oxide may be selected from one of silicon dioxide (SiO2), silicon nitride (Si3N4), hafnium dioxide (HfO2), and aluminum oxide (Al2O3).
[0042] In some optional embodiments, the method for preparing multilayer TMDs on the oxide layer of the substrate can be a mechanical stripping method or a chemical vapor deposition CVD method. Among them, the mechanical stripping method is a commonly used method for preparing two-dimensional materials, such as graphene, TMDs, and its principle is to select a tape with appropriate viscosity for artificial mechanical stripping according to the size of the van der Waals force between the layers of the material. Chemical vapor deposition is a preparation method that can currently achieve mass production.
[0043] In general, the preparation method provided in the above embodiments has the advantages of simple process, realization at room temperature, short preparation cycle, low cost, non-toxicity and pollution-free, and can significantly improve the luminescence efficiency of TMDs.
[0044] In the following content, MoS2 is taken as an example, combined with specific implementation data, the above scheme is described in detail. After knowing the implementation principle of MoS2, those skilled in the art can reuse it in the implementation of other TMDs types with highly similar structures and properties to MoS2, such as WS2, MoSe2, and WSe2. The schematic diagram of high-energy particle irradiation of MoS2 is shown in Figure 2 shown.
[0045] Embodiment 1
[0046] Step (1): Take several 4-inch silicon wafers, photolithography them to form cross marks with numbers, and divide the SiO2 / Si wafers into 1-2 cm 2 A square substrate is prepared, and the substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence at room temperature, and then blown dry with nitrogen;
[0047] Step (2): using adhesive tape on the substrate treated in step (1), and adopting a micromechanical exfoliation method to obtain a MoS2 sample;
[0048] Step (3): Preliminary screening of silicon wafers by observation under an optical microscope to select those with an area larger than 10 μm 2 , MoS2 sample with 2 layers, take a photo and record the number of the cross mark;
[0049] Step (4): Take the MoS2 sample prepared in step (3) and perform 100 KeV, with an injection volume of 5×10 12 p / cm 2 , 5×10 13 p / cm 2 , 5×10 14 p / cm 2 of proton irradiation.
[0050] Step (5): The sample after proton irradiation is subjected to photoluminescence (PL) spectrum test using a Raman spectrometer of the Horiba Company HR-800 model. The test environment is at room temperature and pressure. The specific test parameters are as follows:
[0051] Laser wavelength: 532nm;
[0052] Test power: 10% of maximum power;
[0053] Test range: 550~1000nm;
[0054] Integration time: 5s;
[0055] Number of points: 1 time;
[0056] Objective lens magnification: ×100;
[0057] Grating: 600g / mm;
[0058] The test results are as follows Figure 3 shown in Figure 3 In the figure, the horizontal axis is the wavelength and the vertical axis is the PL spectrum intensity.
[0059] Comparative Example 1
[0060] A 2-layer MoS2 sample was selected from step (3) of Example 1, and a photoluminescence (PL) spectrum test was performed directly using a Horiba HR-800 Raman spectrometer without irradiation. The test environment and test parameters were consistent with those of Example 1. For the convenience of comparison, the test results were plotted in Figure 3 .
[0061] Embodiment 2
[0062] Step (1): Take several 4-inch silicon wafers, photolithography them to form cross marks with numbers, and divide the SiO2 / Si wafers into 1-2 cm 2 A square substrate is prepared, and the substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence at room temperature, and then blown dry with nitrogen;
[0063] Step (2): using adhesive tape on the substrate treated in step (1), and adopting a micromechanical exfoliation method to obtain a MoS2 sample;
[0064] Step (3): Preliminary screening of silicon wafers by observation under an optical microscope to select those with an area larger than 10 μm 2 , MoS2 sample with 3 layers, take a photo and record the number of the cross mark;
[0065] Step (4): Take the MoS2 sample prepared in step (3) and perform 100 KeV, with an injection volume of 5×10 12 p / cm 2 , 5×10 13 p / cm 2 , 5×10 14 p / cm 2 of proton irradiation.
[0066] Step (5): The sample after proton irradiation is subjected to photoluminescence (PL) spectrum test using a Raman spectrometer of the Horiba Company HR-800 model. The test environment is at room temperature and pressure. The specific test parameters are as follows:
[0067] Laser wavelength: 532nm;
[0068] Test power: 10% of maximum power;
[0069] Test range: 550~1000nm;
[0070] Integration time: 5s;
[0071] Number of points: 1 time;
[0072] Objective lens magnification: ×100;
[0073] Grating: 600g / mm;
[0074] The test results are as follows Figure 4 shown in Figure 4 In the figure, the horizontal axis is the wavelength and the vertical axis is the PL spectrum intensity.
[0075] Comparative Example 2
[0076] A 3-layer MoS2 sample was selected from step (3) of Example 2, and a photoluminescence (PL) spectrum test was performed directly using a Horiba HR-800 Raman spectrometer without irradiation. The test environment and test parameters were consistent with those of Example 2. For the convenience of comparison, the test results were plotted in Figure 4 .
[0077] Embodiment 3
[0078] Step (1): Take several 4-inch silicon wafers, photolithography them to form cross marks with numbers, and divide the SiO2 / Si wafers into 1-2 cm 2 A square substrate is prepared, and the substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence at room temperature, and then blown dry with nitrogen;
[0079] Step (2): using adhesive tape on the substrate treated in step (1), and adopting a micromechanical exfoliation method to obtain a MoS2 sample;
[0080] Step (3): Preliminary screening of silicon wafers by observation under an optical microscope to select those with an area larger than 10 μm 2 , MoS2 sample with 4 layers, take a photo and record the number of the cross mark;
[0081] Step (4): Take the MoS2 sample prepared in step (3) and perform 100 KeV, with an injection volume of 5×10 12 p / cm 2 , 5×10 13 p / cm 2 , 5×10 14 p / cm 2 of proton irradiation.
[0082] Step (5): The sample after proton irradiation is subjected to photoluminescence (PL) spectrum test using a Raman spectrometer of the Horiba Company HR-800 model. The test environment is at room temperature and pressure. The specific test parameters are as follows:
[0083] Laser wavelength: 532nm;
[0084] Test power: 10% of maximum power;
[0085] Test range: 550~1000nm;
[0086] Integration time: 5s;
[0087] Number of points: 1 time;
[0088] Objective lens magnification: ×100;
[0089] Grating: 600g / mm;
[0090] The test results are as follows Figure 5 shown in Figure 5 In the figure, the horizontal axis is the wavelength and the vertical axis is the PL spectrum intensity.
[0091] Comparative Example 3
[0092] A 4-layer MoS2 sample was selected from step (3) of Example 3. Without irradiation, a PL spectrum test was performed directly using a Horiba HR-800 Raman spectrometer. The test environment and test parameters were consistent with those of Example 3. For the convenience of comparison, the test results were plotted in Figure 5 .
[0093] Embodiment 4
[0094] Step (1): Take several 4-inch silicon wafers, photolithography them to form cross marks with numbers, and divide the SiO2 / Si wafers into 1-2 cm 2 A square substrate is prepared, and the substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence at room temperature, and then blown dry with nitrogen;
[0095] Step (2): obtaining a MoS2 sample by chemical vapor deposition on the substrate treated in step (1);
[0096] Step (3): Preliminary screening of silicon wafers by observation under an optical microscope to select those with an area larger than 10 μm 2 , MoS2 sample with 4 layers, take a photo and record the number of the cross mark;
[0097] Step (4): Take the MoS2 sample prepared in step (3) and perform 100 KeV, with an injection volume of 4.0×10 8 n / cm 2 , 3.2×10 9 n / cm 2 of neutron irradiation.
[0098] Step (5): After neutron irradiation, the sample was subjected to photoluminescence (PL) spectrum test using a Jobin Yvon HR-800 Raman spectrometer. The test environment was at room temperature and pressure. The specific test parameters were as follows:
[0099] Laser wavelength: 488nm;
[0100] Test power: 300μW;
[0101] Test range: 550~850nm;
[0102] Integration time: 10s;
[0103] Number of points: 1 time;
[0104] Objective lens magnification: ×100;
[0105] Grating: 600g / mm;
[0106] The test results are as follows Figure 6 shown in Figure 6 In the figure, the horizontal axis is the wavelength and the vertical axis is the PL spectrum intensity.
[0107] Comparative Example 4
[0108] A 4-layer MoS2 sample was screened out from step (3) of Example 4, and PL spectrum test was performed directly using Horiba HR-800 Raman spectrometer without irradiation. The test environment and test parameters were consistent with those of Example 4. For the convenience of comparison, the test results were plotted in Figure 6 .
[0109] Result analysis of the embodiment and the corresponding proportion:
[0110] (1) From Figure 3 to Figure 5 It can be seen that compared with before proton irradiation (Comparative Examples 1-3), after proton irradiation (Examples 1-3), the luminescence intensity of the samples was significantly improved. As mentioned above, the improvement of optical performance is mainly achieved by irradiation-induced transformation of multilayer MoS2 from an indirect bandgap semiconductor to a direct bandgap semiconductor. Figure 3 to Figure 5 It can be seen that after different doses of proton irradiation (5×10 12 ~5×10 14 p / cm 2 ), the indirect bandgap luminescence peak originally at 850nm gradually disappeared, leaving only the direct bandgap luminescence peak, which shows that proton irradiation can cause multilayer MoS2 to transform from an indirect bandgap semiconductor to a direct bandgap semiconductor material. The reason for the transformation may be that a certain number of displaced sulfur atoms are produced during proton irradiation, and these sulfur atoms enter the interlayer positions of multilayer MoS2, making the interlayer distance of MoS2 larger and the interlayer force reduced, thereby forming a "quasi-monolayer" structure, making multilayer MoS2 transform from an indirect bandgap to a direct bandgap semiconductor, and ultimately improving the optical properties. However, as the proton injection rate increases further, when the degree of degradation of the optical properties caused by displacement damage is greater than the improvement brought about by the transformation of multilayer MoS2 to a direct bandgap semiconductor, the optical performance after irradiation will deteriorate. Therefore, with the increase of proton irradiation injection, the luminescence intensity first increases and then decreases.
[0111] (2) By Figure 6 It can be seen that compared with the samples before neutron irradiation (Comparative Example 4), the luminescence intensity of the samples after neutron irradiation (Example 4) was significantly improved. 8 n / cm 2 ), the optical properties of MoS2 deteriorate to a certain extent. This is because the defects generated by irradiation are mainly sulfur vacancies Vs. The introduction of Vs will introduce deep defect energy levels in the band gap of MoS2, which will deteriorate the optical properties as non-radiative recombination centers. With the increase of the injection (such as 3.2×10 9 n / cm 2), although Vs is generated, since neutron irradiation is carried out in the air, water and oxygen in the air can be adsorbed during the irradiation process, thereby repairing Vs and performing P-type doping. P-type doping can promote the transformation of negatively charged excitons into neutral excitons, thereby improving the luminescence efficiency.
[0112] Based on the same inventive concept as the aforementioned embodiment, the present invention further provides a transition metal sulfide, which is obtained by the preparation method in the aforementioned embodiment.
[0113] Through one or more embodiments of the present invention, the present invention has the following beneficial effects or advantages:
[0114] The present invention provides a method for preparing transition metal sulfides. By subjecting TMDs to particle irradiation, on the one hand, ex-situ chalcogen atoms can be generated in multilayer TMDs, and these ex-situ chalcogen atoms can enter the interlayer position of MX2, thereby increasing the interlayer distance of XMX, reducing the interlayer force, and promoting the multilayer TMDs to be transformed from an indirect bandgap semiconductor to a direct bandgap semiconductor material, thereby improving the optical efficiency; on the other hand, during the particle irradiation process, the multilayer TMDs can adsorb water molecules or oxygen elements in the air, and promote the transformation of negatively charged trion excitons in the multilayer TMDs into neutral excitons by P-type doping, thereby improving the luminescence efficiency.
[0115] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present application.
[0116] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for preparing transition metal sulfide, It is characterized in that The preparation method comprises: Prepare N layers of transition metal sulfide on a substrate to obtain a sample to be processed; N ≥ 2 and is an integer; Performing particle irradiation on the sample to be processed to improve the luminescence efficiency of the N-layer transition metal sulfide; Wherein, the step of irradiating the sample to be processed with particles comprises: The sample to be processed is irradiated with neutrons in air, and the neutron injection amount is controlled to be 5×10 8 n / cm 2 Up to 10 10 n / cm 2 .
2. The preparation method according to claim 1, It is characterized in that The transition metal sulfide is one of molybdenum disulfide, tungsten disulfide, molybdenum diselenide and tungsten diselenide.
3. The preparation method according to claim 1, It is characterized in that The substrate is a silicon-oxide substrate, and the oxide is one of silicon dioxide, hafnium dioxide, and aluminum oxide.
4. The preparation method according to claim 1, It is characterized in that The method of preparing N layers of transition metal sulfide on a substrate to obtain a sample to be processed comprises: Adhesive tape and transition metal sulfide bulk material are used to prepare N layers of transition metal sulfide on the substrate through a mechanical stripping method to obtain the sample to be processed.
5. The preparation method according to claim 1, It is characterized in that The method of preparing N layers of transition metal sulfide on a substrate to obtain a sample to be processed comprises: N layers of transition metal sulfide are prepared on the substrate by a chemical vapor deposition method to obtain the sample to be processed.
